Home Dialysis Among Elderly Patients: Outcomes and Future Directions. Issue 1 (September 2019) - Auguste, Bourne L.; Chan, Christopher T.
Elderly patients who receive home dialysis (peritoneal dialysis or home hemodialysis) may have reduced survival compared to younger patients. Therefore, it is important to ascertain the goals of home dialysis in the elderly rather than simply fixate on standard metrics such as technique survival. As Canada's population continues to age, the prevalence of end-stage kidney disease among the elderly population is increasing. Patients with multiple comorbidities are now surviving long enough to be started on dialysis. Although home dialysis has been associated with better survival and improved quality of life, its impact on the frail and elderly populations require further elucidation. Home dialysis patients can either independently perform tasks or have support in the home to safely conduct dialysis. Moreover, patients burdened with frailty and multiple comorbidities who lack support in the home may not be able to perform home dialysis safely. Innovative strategies to improve accessibility to home-based therapies need further exploration. In addition, the concept of goal-directed dialysis promotes more individualized treatment. Future continuous quality improvement initiatives must examine if goal-directed dialysis leads to better quality of life outcomes in the elderly.